The Influence of Student Learning, Student Expectation and Quality of Instructor on Student Perceived Satisfaction and Student Academic Performance: Under Online, Hybrid and Physical Classrooms - Firdousi Saba Fazal; Yong Cui; Amir Beenish; Waqar Ayaan (De Gruyter, 2024)
The main aim of this research is to study the influence of traditional, online, and hybrid teaching modes on student academic performance. For this purpose, three determinants of perceived satisfaction and academic performance are used to compare student learning outcomes across the different teaching mediums. This is the first study to examine different teaching modes and their influence on students enrolled in higher education institutions. The study context is a set of China's higher education sector after the COVID-19 outbreak. Data were collected on the model variables through an online questionnaire and distributed amongst a sample of undergraduate students who were enrolled at Overseas Education College at Jiangsu University. Data collection was divided into three categories: pre-pandemic, pandemic, and endemic situations in China. Structural equation modelling technique was adopted to inspect the collected data and confirm the hypothesis. Results show that student learning and student expectations have a significant positive impact on student perceived satisfaction in all contexts. Moreover, online mode of teaching yielded higher level of student satisfaction and hence, their academic performance. Findings of this study have generated implications for stakeholders of the education sector. Teachers must consistently improve themselves in terms of knowledge and skills, while the ministry of education should set required standards and monitor compliance. They should make some courses related to technology and innovation as a part of the undergraduate syllabus. These will help to stay relevant in today's competitive academic sector.